D-π-D hole transport materials based on dioctylfluorene for highly efficient and stable perovskite solar cells without pre-oxidation. (August 2022) - Liu, Xin; Wang, Kexiang; Liu, Ruoyun; Yan, Lei; Dong, Peng; Zhao, Haocheng; Wang, Zhongqiang; Wu, Yuling; Yin, Penggang; Guo, Kunpeng
Abstract: The hole-transporting materials (HTMs) play the decisive effect in the power conversion efficiency (PCE) and the stability of perovskite solar cells (PSCs). In this paper, three D-π-D HTMs (DF-1, DF-2 and DF-3) were prepared by using dioctylfluorene as the π-bridge and three different donor groups, among which DF-3 showed the highest thermal stability, most matched energy levels, and best performance in the undoped PSCs (PCE = 15.21%) due to the introduction of methoxydiphenylamine-substituted carbazole. The doped PSCs prepared based on DF-3 achieved high efficiency (PCE = 19.53%) and good long-term stability (91.4% of the initial PCE after 30 days in air with 10% humidity), which were superior to those with Spiro-OMeTAD as the HTM. Surprisingly, the PCE of DF-3-based doped PSCs reached 18.46% without pre-oxidation due to the high conductivity of DF-3, while the PCE of Spiro-OMeTAD based device was only 7.03%. This work demonstrates that DF-3 can be used for efficient, stable PSCs without pre-oxidation, showing the potential application for real large-scale commercial production in the future. Graphical abstract: Three D-π-D hole transport materials were designed based on dioctylfluorene for the π bridge, among which DF-3 showed higher thermal stability, better hydrophobicity and performance of undoped PSC than DF-1 and DF-2. Compared with Spiro-OMeTAD, DF-3-based doped PSCs exhibit good performance without oxidation, with a maximum PCE of 19.53% and good long-term stability. Image 1 Highlights: Three D-π-D hole transport materials were designed based on dioctylfluorene. DF-3 showed higher thermal stability, better hydrophobicity and performance of undoped PSC than DF-1 and DF-2. Compared with Spiro-OMeTAD, DF-3-based doped PSCs exhibit better performance and long-term stability. DF-3-based PSCs exhibited approximately 96% of the maximum PCE without pre-oxidation.